Invasion and reproduction of Pratylenchus penetrans in birdsfoot trefoil cultivars - Kimpinski, J.; Papadopoulos, Y.A.; Christie, B.R.; McRae, K.B.; Gallant, C.E. (Phytoprotection, 1999)
Greenhouse trials were conducted to determine the levels of invasion of birdsfoot trefoil(Lotus corniculatus) cultivars and lines by the root-lesion nematode (Pratylenchuspenetrans). Numbersof nematodesin roots grown in 50-cm3 polystyrene starter pots were determined 6 weeks after planting. Nematodes were detected in the roots of all cultivars and lines, though the degree of invasion varied significantly. In the first screening trial, carried out in 1994 on 23 cultivars and lines, NB90-104, Upstart, and Viking harbored the lowest population densities of nematodes with levels below 1 000 g-1 of dry root, while Fergus and EPF had population densities over 30 000 g-1 of dry root. In the second screening trial conducted in 1995, all nine cultivars and lines tested, including NB90-104, Upstart, and Viking, had nematode levels greater than 7 900 g-1 of dry root. The results indicated that the cultivars and lines tested in this study exhibited wide genetic variability for invasion by root-lesion nematodes.